Diagnostic Liquid-Based Cytology - Hoda, Rana S.; VandenBussche, Christopher; Hoda, Syed A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
Liquid-based cytology preparations are currently the standard of care for gynecological cytology, and are being increasingly used for non-gynecological cytology. Diagnostic Liquid-Based Cytology serves as a handy guide to diagnostic cytopathology on liquid-based preparations. The authors, renowned experts in the field, provide clear, concise, and practical diagnostic guidance. This handbook equips you to achieve accurate diagnosis of most commonly and uncommonly encountered diseases in exfoliative and aspirated tissue samples from various sites. The key cytopathological features of various diseases are described. The book is lavishly illustrated with dozens of color images that depict the full range of common and rare conditions. Diagnostic Liquid-Based Cytology offers highly practical guidance and information needed to solve common diagnostic challenges in liquid-based cytology preparations. Appropriate histopathological correlations and a consideration of the possible differential diagnosis accompany the cytological findings. The book is an excellent resource not only for practicing pathologists as well as for pathologists-in-training, and will be the perfect practical resource for daily reference in the cytopathology laboratory.
Liquid-Based Specimen Collection, Preparation and Morphology -- Gynecologic Cytology -- Urinary Tract Cytology -- Gastrointestinal Tract Cytology -- Body Cavity Fluids -- Respiratory Exfoliative Cytology -- Fine Needle Aspiration of Thyroid Gland -- Fine Needle Aspiration of Salivary Glands -- Fine Needle Aspiration of Lung -- Cytologic Diagnosis of Lymphoproliferative Disorders by Morphology and Ancillary Techniques -- Fine Needle Aspiration of Pancreas & Liver -- Fine Needle Aspiration of Breast.
Keywords: Medicine; Gynecology; Oncology; Pathology; Medicine & Public Health; Pathology; Gynecology; Oncology